Eksperimentasi Pembelajaran Matematika Dengan Metode Think Pair Share (TPS) Dan Number Head Together (NHT) Ditinjau Dari Prestasi Belajar Dan Kemampuan Komunikasi Matematis Siswa Kelas VII SMP Negeri 2 Banyudono - Okky Wulandari, Yuanita, Idris Harta,M. A, Ph. D (2016)
The purpose of this study is to describe and analyze: (1) the difference in learning methods Think Pair Share (TPS) and Numbered Heads Together (NHT) towards the achievements of the study; (2) the difference in learning methods Think Pair Share (TPS) and Numbered Heads Together (NHT) against mathematical communication skills; (3) the interaction of learning methods Think Pair Share (TPS) and Numbered Heads Together (NHT) towards the achievement of the study and mathematical communication skill. The experiment was conducted on seventh grade in SMP Negeri 2 Banyudono2015/2016 with the entire population of some 278 students of seventh grade student. This research was quantitative with quasi-experimental research designs (quasi-experimental research). Classes that the sample in this study were taken by cluster random sampling method. Methods of data collection using tests and documentation. Data were analyzed by using multivariate analysis of variance. The results of the data analysis with a significance level of 5% was obtained: (1) there is a difference between learning methods Think Pair Share (TPS) and Numbered Heads Together (NHT) to the learning achievement, (2) there are differences in learning methods Think Pair Share (TPS) and Numbered Heads Together (NHT) to mathematical communication skills, (3) there is no interaction learning methods Think Pair Share (TPS) and Numbered Heads Together (NHT) to the learning achievement and mathematical communication skills. Keywords: think pair share (tps), numbered heads together (nht), academic achievement, mathematical communication skills.